The Effectiveness of Occupational Therapy on Patients with Schizophrenia or Another Mental Illness: A Systematic Review - Yuli Anggraini; Ahmad Wahyudi; Dutya Intan Larasati; Ah Yusuf (Universitas Airlangga, 2020)
Introduction: A growing body of literature has shed light on occupational therapy (OT) interventions and outcomes in relation to mental illness. The purpose of this article is to provide an overview of the OT interventions used with patients with schizophrenia or mental illness and their documented outcomes in relation to functional level, well-being and quality of life.Methods: The databases searched were Scopus, Proquest, Sage, and Pubmed and the time of publication was in the last ten years. This was limited by the journal source type. The search terms, truncated when relevant, were